STUDY OF MESH DEPENDENCY ON NUMERICAL MODELING FOR SLOPE STABILITY ANALYSIS BASED ON HOEK-BROWN CRITERIA - Sutriadi
Open pit mining system is a mineral or coal mining system in which all activities are directly related to the outside air. One of the important things that must be considered in mining activities is slope stability, both the stability of the working slope and the final slope. The term slope stability is defined as the resistance of th block on an inclined surface (measured from the horizontal line) against collapsing and sliding (Kliche, 1999). In this study, the slope modeling was modeled using the limit equilibrium method and finite element method in Slide2 and RS2 software with the Hoek-Brown criteria as input parameters. The modeling is done by varying the shape of the elements and the number of points around the slope of 50 to 500 with multiples of 50 with the rock having strain softening and perfect elastoplastic behavior. The number of nodes will result the total number of nodes and the number of elements that has difference to each other, where the more the number of nodes around the slope, the mo re the total number of nodes and the number of elements in the modeling are. The value of the safety factor on the slope depends on the number of points around the slope. The relationship between the factor of safety and the mesh fluctuates and does not continue to decrease with the increase in the number of elements and points, but there is a tendency for the factor of safety to decrease with the increase in the number of elements and the number of points, and will tend to be constant for a large number of nodes. In calculating the slope safety factor using the boundary equilibrium method (FoS=1.451), the results are greater than the finite element method (FoS=1,03).